Caracterização geoambiental da bacia hidrográfica do Rio Saracuruna - RJ: planejamento e gestão - Santos, Wagner de Almeida dos (2009)
The urban area of the city of Rio de Janeiro, mainly around Guanabara Bay, can be considered the state s most important and problematic one, because together with the economic and population growth we can find serious environmental and social problems. In this context is Saracuruna basin and the challenge of its management. This object-area borders some Atlantic Farest preserved sites and has an extremely degraded area, with serious environmental and urban problems, being a natural laboratory where the changes made by man can be observed. This study aims to present the viability of having the river basin as a territory s planning and management unit, providing support so that the upper basin wouldn t suffer the intense environmental damages observed in the lower basin. ln arder to accomplish it Remote Monitoring and Geographic Information System (GIS) techniques were used and some on-thespot surveys were carried out. The results show that the basin, besides having a terribly soil ordenment due to past occupations, suffers with the same mistakes from a recent soil expansion and occupation process, either in the upper, medium ar lower basin. The studied rivers that cross the basin are degraded, almost lifeless. Regarding to the basin environmental quality indicatars based on CONAMA Resolution number 20/86, the sites from which water samples were collected are frequently classified into 2 , 3 and 4 categaries for dissolved oxygen, phosphate, total and fecal colifarm bacteria and pH. Throughout these sites we can notice an intense domestic and industrial waste discharge, garbage, floodplains occupation as well as degradation of the hilisides and vegetation cover. This study points out the urgent need of managing Saracuruna basin, with special attention to the upper basin in arder to find ways to prevent this river to reach irreversible levels of degradation along its whole course. Besides that, measures concerning sanitation, public policies and environmental education must have three basic objectives: social and economic equality, environmental sustainability and economic development.